Between Crónica and Cuento : Alfredo Bryce Echenique's Storied Journal in Guía triste de París - Schwartz, Marcy E. (Pontificia Universidad Católica del Perú. Fondo Editorial, 2004)
A guide to Paris by Alfredo Bryce Echenique could not be anything other than triste. Brycean melancholy, that Proustian sensibility that stretches to both fictional sides of the Atlantic, most permeates his writing in the French capital. Chez Bryce, brooding adolescents, disillusioned artists and writers, and love sick exiles face the daunting Parisian world of residential concierges, diplomatic farce, bourgeois clout and aristocratic posturing. Reminiscent of a popular song form that mixes rhythm and story, the «entries» in Guía triste de París compose a sort of Cole Porter song book of Latin Americans in Paris. The stories' brevity offers an array of narrative tunes rather than positing philosophical or cultural truths about Latin America and Europe and their on-going colonial resonance in the cultural imagination. Bryce incorporates his self-mocking tone into anecdotes that become intimate caricatures. The characters, often autobiographical, are sketched onto the walls and into the neighborhooods of the city. Rather than developing them as psychological entities, their outlines serve to highlight quirky cross-cultural situations. Bryce hurls them against the backdrop of Paris where their idiosyncracies loom and get the better of them.
Páginas [97]-103
Keywords: Bryce Echenique, Alfredo--Guía triste de París; https://purl.org/pe-repo/ocde/ford#6.02.00